Unraveling the LiNbO3 coating layer on battery performances of lithium argyrodite-based all-solid-state batteries under different cut-off voltages. (10th January 2023) - Wei, Chaochao; Yu, Chuang; Chen, Shaoqing; Chen, Shuai; Peng, Linfeng; Wu, Yuanke; Li, Shuping; Cheng, Shijie; Xie, Jia
Abstract: The coating layer can effectively mitigate the undesirable side effects that occur at the active material/sulfide electrolyte interface in the cathode mixture. Plenty of research has reported the coating layer effect in the typical voltage window, while the influence at different voltage windows is unclear. Herein, the degradation mechanism of the bare and LiNbO3 coated LiCoO2 electrodes in all-solid-state batteries when cycled at different cut-off voltages has been systematically investigated. Thecoated electrodes exhibit superior electrochemical performance than the bare electrodes at different charging/discharging rates when the upper cut-off voltage is 3.6 V, while both electrodes show fast degradation of battery performance at higher cut-off voltages (3.9 and 4.2 V). The electrochemical performances are highly dependent on the interfacial stability between the active material and solid electrolyte in the cathode mixture and the structural instability of LiCoO2 at different voltage windows. The evolution of interfacial resistances is systematically investigated in combination of in-situ EIS, relaxation time distribution (DRT), TEM, and XPS. Structural changes of bare and coated LiCoO2 before and after cycled at different cut-off voltages are studied by XRD, TEM, and dQ/dV analysis. The clarification of complex interfaces and phase stability evolution of LiCoO2 provides a strong theoretical basis for constructing high-performance all-solid-state batteries. Graphical abstract: The coating strategy can slow down the volume change of electrode materials and ensure the stability of electrolytes to construct a good solid-state contact. Exploring the difference and applicability of coating strategy under the external conditions of high voltage is crucial for the construction of solid-state batteries with high energy density and long cycles. Image, graphical abstract